Comparative efficacy and safety of Chinese patent medicines as an adjunctive therapy for diabetic peripheral neuropathy: systematic review and network meta-analysis of randomized controlled trials - Qun Wang; Hui Xie; Zihong Wang; Runyun Huang; Min Xu; Yongjun Li; Lingling Shan; Hongyan Zhang; Xianghong Liu; Hongxing Zhang; Yunsheng Xu; Shiguang Sun (Taylor & Francis Group, 2024)
Context Diabetic peripheral neuropathy (DPN) is the most common complication of diabetes mellitus. Chinese patent medicines (CPMs) are widely used in clinical practice to treat DPN.Objective This study aims to summarize the latest evidence on the harms and benefits of CPMs as adjunctive therapy for DPN.Materials and methods We conducted searches for randomized controlled trials (RCTs) evaluating CPMs in conjunction with mecobalamin (Mec) or alpha-lipoic acid (αLA) across eight databases up to July 2024. The surface under the cumulative ranking area (SUCRA) was utilized to assess the clinical efficacy rate (CER), the peroneal motor nerve conduction velocity (pMNCV), the peroneal sensory nerve conduction velocity (pSNCV), the median motor nerve conduction velocity (mMNCV), and the median sensory nerve conduction velocity (mSNCV).Results The search yielded 128 eligible studies with 31 CPMs with Mec and 39 eligible studies with 17 CPMs with αLA. SUCRA rankings indicated that, when combined with Mec, Mailuoning liquid (lMLN) was the most effective regimen for CER, Honghua injection (iHH) for pMNCV, Maixuekang capsule (cMXK) for pSNCV, Dengzhanxixin injection (iDZXX) for mMNCV, and Tongxinluo capsule (cTXL) for mSNCV. Combined with αLA, Danhong injection (iDH) showed the highest efficacy for CER, pSNCV, and mSNCV, while Xueshuantong injection (iXShT) was the most effective for pMNCV and mMNCV.Conclusion This network meta-analysis confirms the efficacy and safety of 37 CPMs combined with Mec or αLA for treating DPN. However, given the potential risk of bias and the very low certainty of the evidence, these recommendations should be adopted with caution.